Social Responsibility and Product Innovation - Iyer, Ganesh; Soberman, David A. (Marketing Science, 2016)
This paper examines the incentives of firms to invest in socially responsible product innovations. Our analysis connects the existence of socially responsible innovations to the presence of intrinsic and extrinsic social responsibility preferences. In addition to deriving economic value from the product, consumers have heterogeneous intrinsic needs to consume products that are socially responsible. They also have extrinsic social comparison preferences that are based on their meetings with others in social interactions. The frequency of these meetings are endogenous to the consumption choices of consumers. A consumer enjoys a social comparison benefit if her consumption decision is more socially responsible than the consumer that she meets in a social interaction and a social comparison cost if it is less socially responsible. The analysis reveals a nonmonotonic effect of social comparison effects on innovation incentives. When the economic value of a product is relatively small, the incentive to innovate decreases as social comparison effects increase. By contrast, when the economic value of a product is sufficiently large, increases in social comparison effects increase the incentive to innovate. Social comparison benefits and costs have different effects on competition between firms. In particular, social comparison benefits soften price competition, whereas social comparison costs tend to exacerbate price competition. We also identify market conditions where a monopoly invests more or less compared to a firm facing competition.